2015
DOI: 10.1128/mcb.00678-15
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Mechanism of TWIST1 Transcription by BHLHE40 and BHLHE41 in Cancer Cells

Abstract: c BHLHE40 and BHLHE41 (BHLHE40/41) are basic helix-loop-helix type transcription factors that play key roles in multiple cell behaviors. BHLHE40/41 were recently shown to be involved in an epithelial-to-mesenchymal transition (EMT). However, the precise mechanism of EMT control by BHLHE40/41 remains unclear. In the present study, we demonstrated that BHLHE40/41 expression was controlled in a pathological stage-dependent manner in human endometrial cancer (HEC). Our in vitro assays showed that BHLHE40/41 suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(73 citation statements)
references
References 55 publications
(86 reference statements)
4
61
1
Order By: Relevance
“…In addition, the similar results observed in the MDA‐MB‐231 cells indicated that the role of BHLHE40 in regulating cell migration and invasion is not restricted to MCF‐7 cells. Although our data and the results of Wu et al indicated that BHLHE40 acts as a pro‐invasion gene in breast cancer and pancreatic cancer, another study has reported an inverse function of BHLHE40 in HEC . This inconsistency remains to be clarified, and tissue specificity may be a reasonable explanation.…”
Section: Disscussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…In addition, the similar results observed in the MDA‐MB‐231 cells indicated that the role of BHLHE40 in regulating cell migration and invasion is not restricted to MCF‐7 cells. Although our data and the results of Wu et al indicated that BHLHE40 acts as a pro‐invasion gene in breast cancer and pancreatic cancer, another study has reported an inverse function of BHLHE40 in HEC . This inconsistency remains to be clarified, and tissue specificity may be a reasonable explanation.…”
Section: Disscussioncontrasting
confidence: 78%
“…Although our data and the results of Wu et al 23 indicated that BHLHE40 acts as a pro-invasion gene in breast cancer and pancreatic cancer, another study has reported an inverse function of BHLHE40 in HEC. 22 This inconsistency remains to be clarified, and tissue specificity may be a reasonable explanation.…”
Section: Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our mRNA expression and bioinformatics analysis identified a large number of additional genes of the ER stress response that are induced by HCoV-229E, such as CHAC1, an enzyme that degrades glutathione [47,48] and others (FICD, HERPUD1, DNAJB9/ERDJ4) functioning as regulators of AMPylation, ubiquitylation or co-chaperones, respectively [49][50][51]. Moreover, HCoV-229E was found to upregulate transcription factors (TFs) with known functions such as EGR1 and c-JUN, but also poorly characterized TFs such as zinc finger (ZNF)165, basic helix-loop-helix-type transcription factors (BHLHE40/41) or zinc finger and BTB domain-containing 43 (ZBTB43) [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of BHLHE41 transcription levels has been characterized as a marker of the progression of several cancers . Recent studies indicate that BHLHE41 is involved in regulating tumour migration and invasion . Asanoma et al demonstrated that BHLHE41 suppressed tumour invasion and metastasis in endometrial cancer by inhibiting TWIST1 transcription.…”
Section: Introductionmentioning
confidence: 99%